UPAYA PENINGKATAN HASIL BELAJAR IPS MELALUI APLIKASI MODEL BELAJAR MIND MAPPING - Sumarno Sumarno (Jurnal Pendidikan, 2013)
The scope of learning material for social sciences (IPS) at Elementary School is very wide, while the time available is very limited. This has been an obstacle for elementary school teachers in achieving the learning objectives. This study aimed to determine whether the application of Mind Mapping learning model on the activities of students learning and the mastery of students learning of IPS. This action research was conducted with three cycles involving 30 students of the fifth grade of elementary school in Kabupaten Kudus. The findings were analyzed using the descriptive qualitative study. The data were collected by using a questionnaires, observation sheets, pretest, and posttest. The results showed that the Learning Model of Mind Mapping can improve the students activity. This indicated an increase in the average score of the class activity to 48.2% in the first cycle, to 56.1% in the second cycle, and to 62.2% in cycle III. The average of the student learning outcomes for IPS also increased from 64 in the first cycle, to 67 in the second cycle, and to 75 in cycles III. Materi IPS di Sekolah Dasar memiliki cakupan materi yang sangat luas, sedangkan waktu yang tersedia sangat terbatas. Hal ini menjadi kendala bagi guru-guru Sekolah Dasar dalam mencapai tujuan pembelajaran. Penelitian ini bertujuan untuk mengetahui apakah dengan penerapan model pembelajaran Mind Mapping dapat meningkatkan aktifitas siswa dalam belajar. Penelitian tindakan kelas yang terdiri atas 3 siklus dan sampelnya adalah siswa kelas V SD Kabupaten Kudus yang berjumlah 30 siswa. Hasil penelitian dianalisa secara deskriptif kualitatif. Pengambilan data dilakukan dengan cara menggunakan angket, lembar observasi, pre-tes dan posttes. Hasil penelitian menunjukkan bahwa Model Pembelajaran Mind Mapping dapat meningkatkan aktifitas siswa. Hal ini ditunjukkan dengan adanya peningkatan skor rata-rata aktifitas kelas yaitu dari 48,2% pada siklus I, 56,1% pada siklus II, dan 62,2% pada siklus yang ke III. Rata-rata hasil belajar siswa untuk mata pelajaran IPS juga meningkat dari 64 pada siklus I, menjadi 67 pada siklus II, dan 75 pada siklus ke III.